2014
DOI: 10.2131/jts.39.551
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the role of silica particle size with mineral fiber geometry in the release of superoxide from rat alveolar macrophages

Abstract: -Particulate air pollutants and mineral fibers activate inflammatory cells to release oxidants, which contribute to inflammation and injury in the lower respiratory tract. Our aim was to compare the role of silica particle size with mineral fiber length and width in the ability to induce superoxide release from rat alveolar macrophages. We estimated the ability of four types of silica particle samples, with different mode diameter, and three types of mineral fiber samples, with different geometric mean lengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We considered to the inconsistency that the fiber length affects to release superoxide from macrophages further than the fiber surface characteristics. In fact, we previously demonstrated that the activity of mineral fiber to induce superoxide release from macrophages was approximately 8.3 times greater than that of silica [12].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We considered to the inconsistency that the fiber length affects to release superoxide from macrophages further than the fiber surface characteristics. In fact, we previously demonstrated that the activity of mineral fiber to induce superoxide release from macrophages was approximately 8.3 times greater than that of silica [12].…”
Section: Discussionmentioning
confidence: 94%
“…The method for measuring lucigenin-dependent CL from the macrophages exposed to various mineral samples has been described in previous reports [9][10][11][12].…”
Section: Measurementsmentioning
confidence: 99%
“…As efforts to reduce incidence of silicosis continue, knowledge of the silica content of specific ranges of particle size will be useful for several reasons: 1) as noted by Qi et al (2015), dust control technologies can be best developed and utilized when the size distribution of the dust and the silica content of different particle size ranges are well understood; 2) the analytical methods used to quantify silica in dust samples are most accurate when the size distribution of silica within the dust sample is closely matched to the size distribution of the calibration material (Huggins et al , 1985; Pickard et al , 1985); and 3) once inhaled, silica particles of distinct sizes may have variable impacts on inflammation and the development of fibrosis (Goldstein and Webster, 1966; Wiessner et al , 1989; Mischler, 2013; Ohyama et al , 2014). This may be further impacted by the enhanced penetration of smaller particles in the alveolar region of the lungs (Bartley and Vincent, 2011).…”
Section: Introductionmentioning
confidence: 99%